Air Quality Monitoring System And Air Neutralizer In Hotel Rooms With Notification Via Telegram - Dasmen, Rahmat Novrianda; Akbar, Rizki (Tech-E, 2023)
Indonesia is rich in natural beauty, and in various regions it presents many tourist objects that attract visitors from various regions and foreign countries. Hotels, as a form of public accommodation, are extremely beneficial to tourists who are traveling by providing lodging services in the form of hotel rooms. The article aims to design a carbon dioxide (CO2) gas detector because CO2 gas is included in air quality and uses the MQ 135 sensor to detect gas in order to provide comfort to hotel visitors. carbon dioxide (CO2), DC fans as air neutralizers in hotel rooms, and with notifications via telegram to find out the levels of carbon dioxide (CO2) gas in hotel rooms.